Natural soundscapes and tourist loyalty to nature-based tourism destinations: the mediating effect of tourist satisfaction. Issue 2 (12th February 2018) - Jiang, Jinde; Zhang, Jie; Zhang, Honglei; Yan, Bingjin
ABSTRACT: The purpose of this study is to explore the effect of natural soundscapes on tourist behaviors in a nature-based tourism destination. A behavioral model depicting the relationship among tourist attitudes to natural soundscapes, natural soundscape image, tourist satisfaction, and loyalty is examined using structural equation model and bootstrapping analysis. Results indicate that tourist attitudes directly affect natural soundscape image but do not affect tourist satisfaction and loyalty. The natural soundscape image directly affects tourist satisfaction and indirectly affects tourist loyalty when mediated by tourist satisfaction. Positioning natural soundscapes as a novel tourism attractor, theoretical and managerial implications are presented.